1982
DOI: 10.1016/0014-5793(82)81335-5
|View full text |Cite
|
Sign up to set email alerts
|

Bromobimane crosslinking studies in oligomycin‐sensitive ATPase from beef heart mitochondria

Abstract: Using a bromobimane fluorescent label the il4,3 1000 protein band oligomycin-sensitive (OS)-ATPase from beef heart mitochondria is shown to become much intensified by 2-mercaptopropionylglycine.In the presence of 3.5 nmol/mg protein of the thiol reagent ATP-Pi exchange activity is increased by 90%. With the fluorescent crosslinking reagent dibromobimane (DB) we show that a new fluorescent peak appears between Mr 50000 and 60000. ATP-Pi exchange is very much decreased by DB. The results suggest that for regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Zimmer and co-workers (18,19) examined the effects of cross-linking reagents including Cu(OP) 2 on an oligomycin-sensitive ATPase preparation from bovine heart mitochondria and found that it modified a 31-kDa protein significantly. Later, Joshi and Torok reported that an ADP/ATP carrier contaminating the preparation of ATPase was the protein modified by Cu(OP) 2 and that Cu(OP) 2 caused intermolecular and intramolecular disulfide bridges in electron transport particles from bovine heart mitochondria (20), but it seemed to induce only intramolecular cross-linking of the carrier present in the preparation of H ϩ -ATPase (21).…”
mentioning
confidence: 99%
“…Zimmer and co-workers (18,19) examined the effects of cross-linking reagents including Cu(OP) 2 on an oligomycin-sensitive ATPase preparation from bovine heart mitochondria and found that it modified a 31-kDa protein significantly. Later, Joshi and Torok reported that an ADP/ATP carrier contaminating the preparation of ATPase was the protein modified by Cu(OP) 2 and that Cu(OP) 2 caused intermolecular and intramolecular disulfide bridges in electron transport particles from bovine heart mitochondria (20), but it seemed to induce only intramolecular cross-linking of the carrier present in the preparation of H ϩ -ATPase (21).…”
mentioning
confidence: 99%
“…As is becoming evident from the foregoing discussion, in mitochondria, oligomycin -sensitive thiol reactivity occurs to a remarkable extent [1,4,7,8,[18][19][20]33,43,57,58,61,62,64,66]. Such mitochondrial -SH reactivity can be also deduced to working rat hearts in experimentation with MPG [65] and alpha lipoic acid [67].…”
Section: Discussionmentioning
confidence: 99%
“…It was also considered very likely that the inhibition of the ATP-Pi exchange activity by NEM was due to its reaction with SH group of the 30 kDa subunit [8]. Conversely, that same subunit of 30-31 kDa was increased in staining intensity together with augmented ATP-Pi exchange by SH reagent 2-mercaptopropionylglycine (MPG) [64]. According to Gaballo et al [22] in the functional state of ATPsynthase, which could be compared to our native enzyme in the presence of ADP, there is a free SH-group at 25-27 kDa protein, the so-called PVP(F01)b subunit (m.w.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-linking reaction should be carried out in a condition that is as close as possible to the native physiological condition and the presence of the cross-linker should not appreciably distort the protein structure from its native conformation. Interestingly, most enzymes to which cross-linkers have been added tend to retain their enzymatic activity (Zimmer et al, 1982). Also, in Section 9, a number of cases where identified crosslinks were found to be in accord with the known structure, with few exceptions, were discussed.…”
Section: Protein Function Cross-linking Reagents Usedmentioning
confidence: 98%